Is systemic lupus erythematosus different in urban versus rural living environment? Data from the Cretan Lupus Epidemiology and Surveillance Registry. (January 2019) - Gergianaki, I; Fanouriakis, A; Adamichou, C; Spyrou, G; Mihalopoulos, N; Kazadzis, S; Chatzi, L; Sidiropoulos, P; Boumpas, D T; Bertsias, G
Background: Examining urban–rural differences can provide insights into susceptibility or modifying factors of complex diseases, yet limited data exist on systemic lupus erythematosus (SLE). Objective: To study SLE risk, manifestations and severity in relation to urban versus rural residence. Methodology: Cross-sectional analysis of the Crete Lupus Registry. Demographics, residency history and clinical data were obtained from interviews and medical records ( N =399 patients). Patients with exclusively urban, rural or mixed urban/rural residence up to enrolment were compared. Results: The risk of SLE in urban versus rural areas was 2.08 (95% confidence interval: 1.66–2.61). Compared with rural, urban residence was associated with earlier (by almost seven years) disease diagnosis – despite comparable diagnostic delay – and lower female predominance (6.8:1 versus 15:1). Rural patients had fewer years of education and lower employment rates. Smoking was more frequent among urban, whereas pesticide use was increased among rural patients. A pattern of malar rash, photosensitivity, oral ulcers and arthritis was more prevalent in rural patients. Residence was not associated with organ damage although moderate/severe disease occurred more frequently among rural-living patients (multivariable adjusted odds ratio: 2.17, p =0.011). Conclusion: Our data suggest that the living environment may influence the risk, gender bias and phenotype of SLE, not fully accounted for by sociodemographic factors.